2018
DOI: 10.1021/acsomega.8b01689
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Chlorophyll-Incorporated Nanogels for Potential Applications in Photothermal Cancer Therapy

Abstract: Nanogels have been widely used in biomedical applications, such as carriers for hyperthermia cancer treatment, drug delivery, and imaging. Owing to the enhanced permeability and retention effect, nanogels have shown a great potential in cancer therapy. In this study, sodium copper chlorophyllin (SCC), a low cytotoxicity and biodegradable photothermal agent, was copolymerized with a nanogel of N-[3-(dimethylamino)propyl]methacrylamide. The nanogels could produce heat under exposure to a green laser with a 532 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…We previously showed that SCC-containing nanogels based on N -[3-(dimethylamino) propyl] methacrylamide (NDPMA) possess a photothermal capacity and could be used for photo-induced hyperthermia therapy [17]. However, the cancer-killing capacity of SCC-containing nanogel could be further improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that SCC-containing nanogels based on N -[3-(dimethylamino) propyl] methacrylamide (NDPMA) possess a photothermal capacity and could be used for photo-induced hyperthermia therapy [17]. However, the cancer-killing capacity of SCC-containing nanogel could be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…The selective absorption property may make green light suitable for photothermal treatment without heating surrounding tissues. Previously, our group fabricated a nanogel composed of sodium copper chlorophyllin (SCC), a photothermal agent absorbing green light, and N -[3-(dimethylamino) propyl] methacrylamide (NDPMA), a positively charged monomer [17]. After being taken up by the cells through electrostatic interactions, the cell-killing efficacy of the SCC-containing nanogel was greatly enhanced via photothermal effect.…”
Section: Introductionmentioning
confidence: 99%
“…As described in the literature, 9 the use of NMR spectroscopy was not suitable to characterize the copolymers due to the presence of paramagnetic Cu 2+ in the ChPh units. Attempts to remove or replace the copper cation with strong acids and other chelating agents were unsuccessful.…”
Section: Degradation Of P(mpeg-chph)mentioning
confidence: 99%
“…Human breast adenocarcinoma cell lines (MCF 7), murine mammary triple-negative carcinoma cell lines (4T1), mouse embryonic fibroblasts (NIH 3T3), and murine fibroblast cell lines (L929) were procured from the Centre for Cellular & Molecular Biology (CCMB), Hyderabad, India. The cell lines were cultured and maintained in DMEM and RPMI medium supplemented with 10% (v/v) FBS, 1% l -glutamine, and 100 U/mL streptomycin/penicillin, in a humidified atmosphere at 37 °C containing 5% CO 2 . …”
Section: Experimental Sectionmentioning
confidence: 99%